High Resolution of Diffusion Reflection and Transmission Spectrum of Hails Potato - A. Alfahhad, Marwan (Asian Journal of Chemistry, 2010)
The mechanism in which electromagnetic radiations interacts with material objects, is a major interesting, investigating, applicable process. Historically, interaction of light with material was first peaked by some of the natural phenomenon of the blue sky, the rainbow and the transparency of some liquids and solids material, whereas some are not showing such observations. Recently with the improvements of laser, it has become more important to understand how electromagnetic radiations, especially optical wavelength travel through biological tissues. The significance of this paper is that the high resolution diffusion reflection and transmission spectrum of Hails potato as a biological sample was completed using the integrating sphere for measuring all the forward transmitted light and the backward reflected light.